Taking a Long View on What We Now Know About Social and Environmental Accountability and Reporting1*) (Issues in Social and Environmental Accounting (ISEA), 2007)
Sustainability and social responsibility appear to be occupying a place of increasing importance in the discourse surrounding business and organisation. As this discourse gains acceptance organisations seek for ways to measure and manage their interactions in the field. Simultaneously, societal concerns for the way in which organisations represent themselves with respect to social responsibility and sustainability stimulate a need for wider accountability. This essay joins a steadily growing trickle of papers which attempt to articulate and make sense of social accounting, accountability and reporting and, in so doing, offer suggestions for future directions in research, teaching and/or practice. The primary purpose of this paper is to offer a view of developments in social accounting in the last decade or so and to emphasise something I fear we are in danger of losing – namely that sense of the importance of social accounting and the considerable critical potential of the social accounting project. The paper provides a brief introduction to the growth in the social accounting literature; a typology of research approaches to the area; and a polemic on the crucial potential importance of social accounting. With this background, the essay then takes a broad review of the social accounting literature and seeks to offer some contentious perceptions on that research in the hope of stimulating debate.